Value-Added Tax (VAT) Implications within the South African environment arising from the classification of cryptocurrencies as financial services under the VAT Act - Hendricks, Rodney Francois (Department of Finance and Tax, 2023)
Cryptocurrencies have been growing rapidly in South Africa (SA) since the initial user alert in 2014 that was issued by National Treasury to South African citizens on the uses of cryptocurrencies. During this time, the number of cryptocurrency merchants, including popular online marketplaces in South Africa that began to accept cryptocurrencies for goods or services, has also increased steadily. This rapid increase in the use of cryptocurrencies prompted the South African Revenue Services (SARS) to issue a media release in April 2018. The main points relevant to this study included inter alia the statement by SARS that the onus is on taxpayers to declare all cryptocurrency related transactions, cryptocurrencies are not legal tender as a means of payment or exchange and not regarded as currency, and, more relevant to this study, that the Value-Added Tax (VAT) treatment of cryptocurrencies would be reviewed. Pending policy clarity in this regard, SARS would not require VAT registration as a vendor for purposes of the supply of cryptocurrencies. After further consultative processes on the classification of cryptocurrencies involving National Treasury and other stakeholders, cryptocurrencies were classified as financial services in 2019. This study was limited to the VAT implications arising from the classification of cryptocurrencies as financial services and did not look at the income tax implications. Also, the study discusses cryptocurrencies in general and not a particular cryptocurrency like Bitcoin. The main objectives of this study were to firstly identify whether there will be a compliance risk or impact to the fiscus through the trading in cryptocurrencies by a vendor resulting in mixed supplies and apportionment issues that could lead to possible VAT leakage, and secondly to compare the classification to cryptocurrencies within the SA VAT system to the approach taken by foreign jurisdictions. The study examined the nature and history of cryptocurrencies, the SA VAT system, the possibility of potential VAT leakage, and drew a comparison of SA VAT legislation to the approach taken by other countries with regards to cryptocurrencies. The findings of this study suggest that there is likely to be a compliance risk with regards to VAT apportionment which has the potential to lead to VAT leakage for the fiscus or alternatively for the taxpayer. The study also found that the treatment that SA has adopted for the classification of cryptocurrencies for VAT purposes is comparable to other countries. Another important finding is also that the European Union (EU) appears to apply a more appropriate and fair method of apportionment than SA, as the EU turnover formula is more flexible and allows for adjustment for potentially distorting items, such as interest and dividends. In SA the debate between taxpayers and SARS as to what constitutes a fair and appropriate apportionment method is ongoing and the results of this study suggest that the classification of cryptocurrencies as financial services is likely to further fuel that debate. This study therefore recommends that SA move towards a more nuanced basis of apportionment in instances of mixed supplies.